Woman of god - Patterson, James, 1947-; Paetro, Maxine (Little, Brown and Company, 2016)
"St. Peter's Square, Rome. White smoke signals that a new Pope has been chosen. Is it possible that the new Pope is a woman? The world is watching as historic crowds gather in Rome, waiting for news of a new Pope, one who promises to be unlike any other in the Church's history. Some followers are ecstatic, but the leading candidate has made a legion of powerful enemies. From a difficult childhood with drug addled parents, to a career as a doctor on the front lines in Sudan, to a series of trials that test her faith at every turn, Brigid Fitzgerald's convictions and callings have made her the target of all those who fear that the Church has lost its way, dangerous adversaries who abhor challenges to tradition. Locked in a deadly, high-stakes battle with forces determined to undermine everything she believes in, Brigid must convert her enemies to her cause before she loses her faith and her life"--